(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2025)
The ketogenic diet is emerging as an effective therapeutic option for patients with neurological disorders. The diet results in metabolism of fatty acids to ketone bodies like ?-hydroxybutyrates (BHBs), which serve as an alternative fuel source for brain cells. However, the molecular effect of BHB on neurons is not well understood. We hypothesized that BHB administration will induce upregulation of energy metabolism-related processes in neurons. To assess the effect of BHB administration on the neuronal transcriptome, we reanalyzed a publicly available RNAseq dataset (GSE252513) using a bioinformatic “3-pod” approach. We conducted pathway analysis and identified leading edge genes using Gene Set Enrichment Analysis (GSEA) and conducted chemical perturbagen analysis using the iLINCS repository to identify drugs that are concordant and discordant with BHB administration. We identified significantly altered (p<0.05) pathways associated with inflammation and immunity such as “regulation of proinflammatory cytokine production” and “modulation of inflammatory responses.” We did not identify significant modulation of energy metabolism-related pathways in response to BHB administration. Our results suggest that under normal conditions, BHBs primary actions include modulation of cellular neuronal immune responses.